2011
DOI: 10.3184/095422911x13103191328195
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical characterization of lead in three shooting range soils in Florida

Abstract: To better understand the environmental impact of lead (Pb) in shooting range soils, Pb levels in three berm soils were characterized via size distribution, total Pb concentration, water-soluble Pb, sequential extraction and X-ray diffraction (XRD). About 60% of the mid-berm soils of ranges-G and -O existed in grain sizes between 0.5 and 0.25 mm (medium sand) while range-L was most abundant in the 0.25 -0.106 mm (fine sand) size fraction. All three range soils had the most accumulation of lead (60 -70%) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…32 The partitioning of Pb in the different soil fractions is largely dependent on the chemistry and geochemistry of the soil such as its pH, cation exchange capacity, organic matter content and presence of other chemicals in the soil. The sequential extraction method takes place with the assumption that the partitioning of the metal within each fraction is lowered with each successive extraction step.…”
Section: Pb Partitioning and Availability In Shooting Range Berm Soilsmentioning
confidence: 99%
“…32 The partitioning of Pb in the different soil fractions is largely dependent on the chemistry and geochemistry of the soil such as its pH, cation exchange capacity, organic matter content and presence of other chemicals in the soil. The sequential extraction method takes place with the assumption that the partitioning of the metal within each fraction is lowered with each successive extraction step.…”
Section: Pb Partitioning and Availability In Shooting Range Berm Soilsmentioning
confidence: 99%
“…Numerous studies have reported elevated concentrations of PTEs in soil samples collected from war-impacted areas and military training grounds [6,7,9,13,[15][16][17][19][20][21][22][23][24][26][27][28][29][63][64][65][66][67][68][69][70] with their reported values summarized in Table 3.…”
Section: Soil Contamination By Potentially Toxic Elementsmentioning
confidence: 99%
“…An understanding of metal partitioning in soils may be used to maximise the removal efficiencies of the metals from the soil. Most firing ranges have lead primarily associated with the carbonate fraction, which can be solubilised by the addition of acidic reagents such as citric acid (Fayiga et al 2011).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%